Humanizing Modern Medicine An Introductory Philosophy of Medicine - Marcum, James A.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2008)
In this book the author explores the shifting philosophical boundaries of modern medical knowledge and practice occasioned by the crisis of quality-of-care, especially in terms of the various humanistic adjustments to the biomedical model. To that end he examines the metaphysical, epistemological, and ethical boundaries of these medical models. He begins with their metaphysics, analyzing the metaphysical positions and presuppositions and ontological commitments upon which medical knowledge and practice is founded. Next, he considers the epistemological issues that face these medical models, particularly those driven by methodological procedures undertaken by epistemic agents to constitute medical knowledge and practice. Finally, he examines the axiological boundaries and the ethical implications of each model, especially in terms of the physician-patient relationship. In a concluding Epilogue, he discusses how the philosophical analysis of the humanization of modern medicine helps to address the crisis-of-care, as well as the question of "What is medicine?" The book's unique features include a comprehensive coverage of the various topics in the philosophy of medicine that have emerged over the past several decades and a philosophical context for embedding bioethical discussions. The book's target audiences include both undergraduate and graduate students, as well as healthcare professionals and professional philosophers.
Metaphysics -- Medical Worldviews -- Medical Causation and Realism -- Patient as Body or Person -- Disease or Illness and Health or Wellbeing -- Diagnosis and Therapeutics -- Epistemology -- Medical Thinking -- Clinical Judging and Decision Making -- Medical Explanations -- Diagnostic Knowledge -- Therapeutic Knowledge -- Ethics -- Medical Axiology and Values -- Origins of Bioethics and Normative Ethics -- Principlism and the Future of Bioethics -- Emotionally Detached Concern or Empathic Care -- Patient-Physician Relationships.
Keywords: PHILOSOPHY (GENERAL).; MEDICINE; GENETIC EPISTEMOLOGY; ETHICS; METAPHYSICS; MEDICINE -- PHILOSOPHY; PHILOSOPHY; PHILOSOPHY OF MEDICINE; BIOMEDICINE GENERAL; EPISTEMOLOGY; ETHICS; METAPHYSICS